Functionalization of the electronic and magnetic properties of silicene by halogen atoms unilateral adsorption: a first-principles study. (14th August 2018) - Mao, Yuliang; Xu, Haiqiao; Yuan, Jianmei; Zhong, Jianxin
Abstract: Based on first-principles calculations, the structure, electronic and magnetic properties of unilateral halogenated silicene Si2 X1 (X  =  F, Cl, Br, I) are investigated. The formation energies of all the configurations of studied Si2 X1 (X  =  F, Cl, Br, I) are found to be lower than that in pristine silicene, which indicates the strong stability. The band structure of half-fluorinated configuration Si2 F1 presents metallic property, while other unilateral halogenated silicene Si2 X1 (X  =  Cl, Br, I) exhibits half-metallic properties. In unilateral halogenated silicene Si2 X1 (X  =  Cl, Br, I), the unpaired electrons in unsaturated silicon atom produce the localized magnetic moment. However, due to the strong electronegativity in F atom, the half-fluorinated silicene Si2 F1 is almost non-magnetic. The metallic property of Si2 F1 configuration can be tuned to half-metallic by applying biaxial tensile strain from 11.95% to 13.51%. Furthermore, applying biaxial tensile strains can tune the half-metallic property of unilateral halogenated silicene Si2 X1 (X  =  Cl, Br, I) to a semiconductor. This half-metallic property in unilateral halogenated silicene Si2 X1 (X  =  Cl, Br, I) can be recovered and can even be tuned to metallic if continually increasing the biaxial tensile strains.